2008
DOI: 10.1111/j.1745-7262.2008.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Emodin induces apoptosis in human prostate cancer cell LNCaP

Abstract: In prostate cancer cell line, LNCaP, emodin inhibites the proliferation by AR and p53-p21 pathways, and induces apoptosis via the mitochondrial pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…These results are in line with previous studies. Emodin induced apoptosis of LNCaP cells through the alterations in expression of Bax and Bcl2 genes which had the same result as ours (21). In another study, the increased Bax concurrent with the decrease of Bcl-2 indicated that emodin induces apoptosis in human chronic myeloid leukemia K562 cell lines (22).…”
Section: Discussionsupporting
confidence: 69%
“…These results are in line with previous studies. Emodin induced apoptosis of LNCaP cells through the alterations in expression of Bax and Bcl2 genes which had the same result as ours (21). In another study, the increased Bax concurrent with the decrease of Bcl-2 indicated that emodin induces apoptosis in human chronic myeloid leukemia K562 cell lines (22).…”
Section: Discussionsupporting
confidence: 69%
“…Emodin, 1,2,8-trihydroxy-6-methylanthraquinone, is an active component contained in the root and rhizome of Rheum palmatum L. (Polygonaceae). Wogonin is one of the primary active compounds of Scutellaria baicalensis, and decreases prostate cancer cells in a p53-dependent mechanism [2,3]. The MDM2 antagonist Nutlin-3 specifically inhibits proliferation of LNCaP cells through cell cycle arrest and apoptosis by increasing levels of p53-responsive p21 and MDM2 expressions, demonstrating that MDM2 antagonists retain functional p53 and androgen receptor signaling in human prostate cancers [4].…”
Section: Introductionmentioning
confidence: 99%
“…The MDM2 antagonist Nutlin-3 specifically inhibits proliferation of LNCaP cells through cell cycle arrest and apoptosis by increasing levels of p53-responsive p21 and MDM2 expressions, demonstrating that MDM2 antagonists retain functional p53 and androgen receptor signaling in human prostate cancers [4]. Melatonin, a circadian indoleamine hormone secreted by the human pineal gland, is able to directly induced cell death of several types of human tumor cells [1][2][3][4][5][6][7][8][9]. Many recent reports have shown that melatonin inhibits the growth of androgen-sensitive human LNCaP prostate cancer cells [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Prostate cancer is induced by various factors such as age, genetics, diet, race, lifestyle and medication, and the rate of mortality caused by prostate cancer is increasing. 27,28) Interestingly, HIF-1a overexpression is associated with the growth and metastasis of rat and human prostate cancer cell lines. 29) During the growth of prostate cancer, hypoxia causes low tissue oxygen and activates the expression of HIF-1a.…”
Section: Discussionmentioning
confidence: 99%